SURFACE OZONE IN KIEV - Shavrina, A. V.; Mikulskaya,, I. A.; Kiforenko, S. I.; Blum, O. B.; Sheminova, V. A.; Veles, A. A. (Одеські астрономічні публікації, 2009)
The study of total ozone over Kiev and its concentration changes with height in the troposphere has been made on the base of ground-based observations with the infrared Fourier-spectrometer in the Main Astronomical Observatory of National Academy of Sciences of Ukraine (MAO NASU) as part of ESA-NIVR-KNMI project no 2907 "OMI validation by ground based remote sensing: ozone columns and atmospheric profiles "(2005-2008) [1,2,4]. Ground-level ozone in Kiev for an episode of its high concentrations in August 2000 was also simulated with the model of urban air pollution UAM-V [5,6]. In 2008 the satellite data Aura-OMI on profiles of ozone in the atmosphere OMO3PR became available (http://disc.sci.gsfc.nasa.gov/ Aura/data-holdings/OMI/ omo3pr_v003.shtml). They include ozone content in the lower layer of the atmosphere, beginning from 2005, which can be used to evaluate the ground-level ozone in all cities of Ukraine. The comparison of the data of ozone air pollution in Kiev (ozone - the pollutant of the first class of danger) and medical statistics data of of respiratory system (RS) diseases of the city population was carried out with the package "Statistica". A regression analysis, prognostic regression modelling, and retrospective prognosis of the epidemiological situation with respect to RS pathologies in Kiev in 2000-2006 were performed.